Kinship and Social Integration: Ethnographic Study of Shia and Sunni Alawiyin Relations in Palembang - Noupal, Muhammad; Supriyanto, John (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study aims to examine in depth the dynamics of social relations between the Shia Alawiyin and Sunni Alawiyin groups in Palembang City. Despite differences in their schools of thought, these two groups are able to coexist without causing open conflict, a condition rarely studied in the literature on intra-community Muslim relations. The knowledge gap lies in the lack of understanding of how kinship ties function as a determining factor in reducing the potential for sectarian conflict. This study uses a qualitative approach with a case study design, involving 12 purposively selected participants. Data collection techniques were carried out through participant observation and in-depth interviews, then analyzed using the ethnographic framework of Spradley and McCurdy. The results show that social relations between Shia and Sunni Alawiyin form associative and dissociative patterns. The associative pattern is reflected in the form of cooperation in the fields of trade, da'wah, and involvement in socio-religious activities. The dissociative pattern is characterized by limited failure that does not develop into open conflict. The most important factor in mitigating potential conflict is the strength of kinship ties (jama'ah) among the Alawiyin. Theoretically, these findings contribute to the study of social integration in pluralistic societies, while practically, they emphasize the importance of strengthening family and cultural solidarity in maintaining social harmony.